O ensino de história no contexto da reforma curricular: uma análise a partir do Documento Curricular do Território Maranhense - BELFORT, Mário Jorge Araujo (2025)
The Maranhão Territory Curricular Document (DCTM), approved in December 2018, is a curricular policy that corresponds to the process of “implementing” the BNCC in the educational context of Maranhão. It presents guidelines for Early Childhood Education and Elementary Education and recommends that public and private schools in the state of Maranhão reformulate their political-pedagogical projects and teachers‟ lesson plans. Thus, based on the understanding that the BNCC premises are contained in the DCTM guidelines, especially with regard to the competency-based teaching and learning process, the general objective of this research is to investigate the history component of the DCTM in the context of curricular reforms, analyzing to what extent and in what sense it expresses the neoliberal assumptions that underlie the BNCC. Methodologically, this research is bibliographical and documentary in nature. In the documentary analysis, the general competencies and the curricular organizer of the History component of both the DCTM and the BNCC were analyzed. Data analysis was supported by content analysis, proposed by Laurence Bardin (2016). Data interpretation was theoretically referenced in studies by Silva (1999; 2012), Lopes (2004; 2006), Duarte (2004), Silva (2003; 2008), Ball (2001; 2008; 2014), Ball and Bowie (1992), Goodson (1997), Gadelha Costa (2009), Silva (2016), Laville (1999), among others. The criterion for choosing these references is justified because they have relevant contributions to understanding the epistemological, political and cultural disputes surrounding neoliberal curricular reforms and their implications for history teaching. We conclude that the history component of the DCTM is aligned with the BNCC guidelines from a homogenizing perspective, where the list of competencies and the curricular design containing the Thematic Units, Objects of Knowledge and Skills to be developed are clearly reproduced, consequently leading to a utilitarian, technical and instrumental conception of history teaching. Thus, it presents itself as limited in terms of knowledge about the reality of Maranhão from a critical perspective, demonstrating commitments to a neoliberal educational model.